1970
DOI: 10.1136/bmj.3.5719.388
|View full text |Cite
|
Sign up to set email alerts
|

Monoamine oxidase inhibitors and L-dopa.

Abstract: The increasing use of L-dopa in the treatment of Parkinsonism has drawn attention to the way in which this catecholamine precursor may interact with other drugs commonly given to such patients. It was reported (Degkwitz et al., 1960) that a monoamine oxidase (M.A.O.) inhibitor potentiated the pressor effect of intravenous L-dopa in psychiatric patients, and a similar effect has been shown in Parkinsonian patients given L-dopa by mouth (Barbeau et al., 1962). In view of the large doses of L-dopa now being given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1971
1971
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(20 citation statements)
references
References 7 publications
1
19
0
Order By: Relevance
“…Ten days later, levodopa 50 mg was aded orally. Blood pres sure changed from 140/90 to 200/120 mm [144], This has been confirmed by another similar report [147], Chlordiazepoxide ad ministered to a parkinsonian patient stabi lized on levodopa has been reported to have markedly reduced the levodopa effect. Dis continuation of chlordiazepoxide brought parkinsonism under control [148], Phenothiazines [149.…”
Section: A Ntiparkinsonian Drugssupporting
confidence: 73%
“…Ten days later, levodopa 50 mg was aded orally. Blood pres sure changed from 140/90 to 200/120 mm [144], This has been confirmed by another similar report [147], Chlordiazepoxide ad ministered to a parkinsonian patient stabi lized on levodopa has been reported to have markedly reduced the levodopa effect. Dis continuation of chlordiazepoxide brought parkinsonism under control [148], Phenothiazines [149.…”
Section: A Ntiparkinsonian Drugssupporting
confidence: 73%
“…As the majority of parkinsonian patients treated with levodopa experience more or less troublesome side effects, any effective levodopa-sparing mechanism is of high practical importance. Clinical studies revealed, however, that the nonselective MAO-inhibitors, in clinical use at present, are definitely contraindicated in patients taking levodopa because hypertensive crises may result (Hunter et al, 1970). It is even recommended to withdraw an MAO inhibitor a month prior to levodopa administration (cf.…”
Section: The Possible Share Of the Blockade Of Mao-b In The Effect Ofmentioning
confidence: 95%
“…At present the use of MAO inhibit0rs is considered to be definitely contraindicated in parkinsonian patients treated with levodopa, because hypertension may result (cf. Hunter et al, 1970).…”
mentioning
confidence: 95%
“…MAO-A/B mixed inhibitors may be efficacious in the inhibition of dopamine metabolism and the treatment of PD (30,32), but there are some side effects of increasing the blood pressure in the presence of a non-selective monoamine oxidase (MAO)-A/B inhibitor or a selective MAO-A inhibitor, L-DOPA increased blood pressure in both PD patients and rats (4,33). These results indicate that L-DOPA exerts directly on its vasoconstrictive effect without conversion to dopamine.…”
Section: Discussionmentioning
confidence: 99%